Perceptions of management accounting students about employability skills acquired at an open distance learning institution - Shuttleworth, CC; Berry, PR; Lötter, M; Viviers, GM; Leonard, C (South African Journal of Higher Education, 2016)
Rapid changes in the global business environment and the changing role of management accountants are placing increasing pressure on higher education institutions to enhance the employability skills and attributes of future management accountants. This article reflects critically on the level to which students are satisfied that an open distance learning (ODL) institution, with specific reference to the University of South Africa (Unisa), can adequately impart the necessary skills to management accounting graduates to enable them to enter the workplace with confidence and become rapidly productive. Web-based surveys were sent to 3 222 third-year management accounting students studying at Unisa. The findings reveal that in general ODL meets and exceeds the responding students’ expectations regarding the enhancement of their employability skills. However, some of the responses indicated that ODL students want the best of both worlds – not only the flexibility, open access and opportunity to work and study according to what the ODL system has to offer, but also the social interaction, face-to-face contact with lecturers and network opportunities offered by residential universities. The results of the study suggest ways to prepare ODL-students for the workplace.